A novel chitosan based fluorescence chemosensor for selective detection of Fe (III) ion in acetic aqueous medium - Pournaki, Mehrad; Fallah, Amirhossein; Gulcan, Hayrettin Ozan; Gazi, Mustafa (Taylor & Francis Ltd, 2021)
Within this study, we have prepared 3-hydroxy-6H-benzo[c]chromen-6-one analogue grafted chitosan polymer. Mainly, 3-(3-chloropropoxy)-6H-benzo[c]chromen-6-one was synthesized from urolithin B and it was grafted on medium molecular weight chitosan (Uro-g-Ch). Employing our previous experience and observation on the characterisation of Urolithin B as a selective, fluorescent probe for sensing Iron (III), we have questioned its application in a polymer chain. Following that, we have conducted a serious of experiments to identify the fluorometric properties of the grafted polymer. Employing the lambda max values detected for excitation and emission of fluorescent active-grafted polymer, the quenching effect of various metals on fluorescence was investigated based on grafted polymer-metal interactions. It was found that the grafted polymer displayed selective interaction with Iron (III) among the other metals tested (e.g. various +1, +2, +3 metals).
Keywords: Chitosan; urolitin B; iron(III) ion; fluorescent; chemosensor; selective detection